2018
DOI: 10.1016/j.amc.2018.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of the modified error function

Abstract: In this article, we obtain explicit approximations of the modified error function introduced in Cho, Sunderland. Journal of Heat Transfer 96-2 (1974), 214-217, as part of a Stefan problem with a temperature-dependent thermal conductivity. This function depends on a parameter δ, which is related to the thermal conductivity in the original phase-change process. We propose a method to obtain approximations, which is based on the assumption that the modified error function admits a power series representation in δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…The method described in [1] had already been considered by Cho and Sunderland in [2] for the analogous Stefan problem with constant heat capacity, corresponding to γ = 0 in (1.1). The modified error function for the case when γ = 0 and δ > 0 was studied by the authors in [3,4] (see also [5]), where existence and uniqueness in the space of bounded analytic functions were proven and explicit approximations were provided (see [6] for improved approximations). In particular, this paper extends the existence and uniqueness result in [3] for the case δ < 0 (γ = 0).…”
mentioning
confidence: 99%
“…The method described in [1] had already been considered by Cho and Sunderland in [2] for the analogous Stefan problem with constant heat capacity, corresponding to γ = 0 in (1.1). The modified error function for the case when γ = 0 and δ > 0 was studied by the authors in [3,4] (see also [5]), where existence and uniqueness in the space of bounded analytic functions were proven and explicit approximations were provided (see [6] for improved approximations). In particular, this paper extends the existence and uniqueness result in [3] for the case δ < 0 (γ = 0).…”
mentioning
confidence: 99%
“…To exhibit the usefulness of the results derived here we have compared the correction terms ϕn(x) in (1.4) with the results obtained by Ceretani et al [18] in Fig.1. It is observed that the lack of monotonicity of successive corrections of MEF present in [18] disappears.…”
Section: Definition 21mentioning
confidence: 88%
“…of MEF was overlooked. In their studies [17,18] and references therein, Tarzia and his collaborators investigated the mathematical aspects of MEF as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations